2012
DOI: 10.5296/ijafr.v2i2.2145
|View full text |Cite
|
Sign up to set email alerts
|

Board Characteristics and Firm Performance: Case of Saudi Arabia

Abstract: Corporate governance (CG) has received much attention in the current studies all over the world especially after many corporate scandals and the failures of some biggest firms around the world such as Commerce Bank (1991) Enron (2001), Adelphia (2002), and World Com (2002). The aim of this study is to examine the relationship between board mechanisms (audit committee size, audit committee composition, board size, and board composition) and firm performance (ROA) based on the annual reports of listed companies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
74
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 91 publications
(95 reference statements)
12
74
1
5
Order By: Relevance
“…On the contrary, the result found insignificant association between audit committee size and Tobin`s Q. Consequently, hypothesis H9 is not supported. The result of this study was similar with those of previous scholars like Abdurrouf (2011), Ghabayen (2012, Kajola (2008), Kim and Yoon (2007), Kyereboah-Coleman (2007), Mohd (2011), Mohd et al (2009), Nuryanah andIslam (2011) and Wei (2007).A probable reason for the insignificant finding of audit committee size and Tobin`s Q is that the firms concentrated on the AC effectiveness as opposed to their sizes as they do not deem AC size to be an important factor in improving the committee's effectiveness. For the effectiveness of AC, it should be made up of independent, expert and well-informed members and should wield sufficient authority (Mohiuddin & Karbhari, 2010).…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 92%
See 1 more Smart Citation
“…On the contrary, the result found insignificant association between audit committee size and Tobin`s Q. Consequently, hypothesis H9 is not supported. The result of this study was similar with those of previous scholars like Abdurrouf (2011), Ghabayen (2012, Kajola (2008), Kim and Yoon (2007), Kyereboah-Coleman (2007), Mohd (2011), Mohd et al (2009), Nuryanah andIslam (2011) and Wei (2007).A probable reason for the insignificant finding of audit committee size and Tobin`s Q is that the firms concentrated on the AC effectiveness as opposed to their sizes as they do not deem AC size to be an important factor in improving the committee's effectiveness. For the effectiveness of AC, it should be made up of independent, expert and well-informed members and should wield sufficient authority (Mohiuddin & Karbhari, 2010).…”
Section: Regression Results Of Model (Based On Marketing Measure)supporting
confidence: 92%
“…, , Dar et al (2011), Ghabayen (2012, Khan and Javid (2011), Kota and Tomar (2010), Kyereboah-Coleman (2007) and Mohd et al (2009). Based on the above arguments, the researcher proposes the following hypothesis;…”
Section: Audit Committee Independence and Firm Performancementioning
confidence: 99%
“…Thus, hypothesis H1 is not supported. This result is consistent with previous studies of Wei (2007) in China, Ghabayen (2012), Mohd (2011) and Nuryanah and Islam (2011) Dar et al (2011) andGhabayen (2012). One possible reason for insignificant result of audit committee independence is that it may be significant to appoint individuals with technical expertise and experience in order to guarantee value creation.…”
Section: Multiple Linear Regression Analysissupporting
confidence: 91%
“…For example, Fallatah and Dickins (2012), Al-Matari et al (2012b), andGhabayen (2012) found no relation between governance mechanisms and firm performance such as board size, board independent, board meeting, audit committee size and audit independent. however, Al-Ghamdi and rhodes (2015) found positive and significant relation between the aforementioned mechanisms and firm performance especially in family firms.…”
Section: Resultsmentioning
confidence: 99%